Leaf plasticity contributes to plant anti-herbivore defenses and indicates selective foraging: Implications for sustainable grazing - Xiliang Li (Elsevier, 2021)
More accurate determination of leaf plasticity induced by the legacy effect of grazing and immediate ingestion can provide insights on growth–defense tradeoffs, and are of great importance to understanding valuable indicators for grassland management. Despite the ecological importance of leaf traits, the effectiveness of leaf plasticity as a key physical anti-herbivore trait that may signal grazing disturbance has not yet been assessed. Here, we assessed leaf angle and related functional traits as indicators of the responses of palatable Leymus chinensis and less palatable Carex korshinskyi to five sheep grazing intensities during the early grazing season. Grazing significantly increases leaf angle, paralleled by a decrease in the sizes of both whole plants and leaves, with a stronger response by L. chinensis than C. korshinskyi. Leaf size and angle had higher positive and lower negative allometric slopes with plant size in L. chinensis compared to C. korshinskyi. This pattern reflects that the palatable species had relatively higher adaptability to grazing via stabilizing leaf area and anti-herbivore defense responses. Structural equation modeling shows that historical grazing contributes more than foraging in the current year to leaf plasticity, which is particularly evident in the less palatable species C. korshinskyi. The foraging proportion is positively correlated with the leaf angle for L. chinensis but not C. korshinskyi, suggesting that leaf plasticity can indicate selective foraging. Moreover, plasticity in leaf angle potentially influences net photosynthesis which manifests as a unimodal curve across the grazing intensities under a balance between the gross photosynthetic and respiratory rates. Thus, we demonstrate that palatability-dependent leaf plasticity can indicate selective foraging across grazing intensities, thereby contributing to plant anti-herbivore defense. Our results highlight that grazing legacy and immediate ingestion had a positive interaction effect on leaf traits. These findings show that grazing-induced leaf plasticity represents a key nexus between ecological mechanisms and grassland management.